2007
DOI: 10.1124/mol.107.041707
|View full text |Cite
|
Sign up to set email alerts
|

Direct Role of Streptozotocin in Inducing Thermal Hyperalgesia by Enhanced Expression of Transient Receptor Potential Vanilloid 1 in Sensory Neurons

Abstract: Streptozotocin (STZ) is a diabetogenic agent extensively used to induce diabetes and to study complications including diabetic peripheral neuropathy (DPN). While studying the influence of transient receptor potential vanilloid 1 (TRPV1) on DPN in the STZ-induced diabetic mouse model, we found that a proportion of STZ-treated mice was nondiabetic but still exhibited hyperalgesia. To understand the mechanism underlying this phenomenon, dorsal root ganglion (DRG) neurons and stably TRPV1 expressing human embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 47 publications
5
77
0
Order By: Relevance
“…However, it has been shown that STZ can directly stimulate DRG neurons and induce thermal hyperalgesia without affecting blood glucose levels (Pabbidi et al, 2008). Concurrent with the increase in blood glucose levels, a significant decrease in the withdrawal threshold was observed 1 day after treatment with 200 mg/kg STZ (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…However, it has been shown that STZ can directly stimulate DRG neurons and induce thermal hyperalgesia without affecting blood glucose levels (Pabbidi et al, 2008). Concurrent with the increase in blood glucose levels, a significant decrease in the withdrawal threshold was observed 1 day after treatment with 200 mg/kg STZ (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…In many instances, neuropathic pain occurs as a direct result of hyperexcitable DRG neurons. Indeed, streptozotocin, an NAD ϩ -depleting agent and pancreatic ␤-cell toxin, used to induce experimental diabetes in animal models, is directly toxic to sensory neurons resulting in measurable thermal hyperalgesia before hyperglycemia ensues (Pabbidi et al, 2008). These would suggest that a direct coupling might exist between resting NAD ϩ levels and the intrinsic firing properties of DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, an approach to assess the potential correlation between the 2 pathophysiological outcomes of diabetes (peripheral neuropathy and visceral hypersensitivity) deserves researchers' attention in future studies. STZ, in a bell-shaped concentration-dependent manner, can directly act on sensory neurons to upregulate transient receptor potential vanilloid type 1 and consequently induce thermal hypersensitivity, 23 based on which one could speculate that the visceral hypersensitivity in the 48% of our diabetic rat model might result from STZ-induced sensitization of sensory neurons, not necessarily from STZ-induced diabetes and associated neuropathy. This speculation needs assumptions that the concentration of STZ in sensory ganglia is in the effective dose range (20-200 M) after a single neonatal injection of 90 mg/kg STZ, and the STZ-induced sensitization of sensory neurons could persist for 8 weeks.…”
Section: Visceral Sensory Responses To Colorectal Distensionmentioning
confidence: 94%